FACTORS AFFECTING AUDIT DELAY IN BASIC AND CHEMICAL INDUSTRIES - Isieny Wendy; Vonni Rizal; Hantono Hantono (Berkala Akuntansi dan Keuangan Indonesia, 2019)
This study aims to examine and analyze the effect of public account firm, complexity of company operations, and total assets to audit delay at basic and chemical industry listed on the Stock Exchange period 2012-2016. The research method used in this research using quantitative approach method, research type is descriptive quantitative which is explanatory research. The population of research is 65 financial report of mining company, with technique of taking purposive sampling hence obtained sample of research as many as 22 financial report of mining company period 2012-2016. Data analysis method in this research is logistic regression analysis. The results of this study show simultaneously public account firm, complexity of company operations, and total assets haven’t a significant effect on the audit delay on basic and chemical industry listed on the Stock Exchange period 2012-2016, with a significant value of 0.020 < 0.05. Partially public account firm, complexity of company operations, and total assets have no effect to audit delay on Mining companies listed in BEI period 2011-2015 with significant value < 0,05. The result of Nagelkerke's R Square value in this research is 0.31 which can be stated that variability of the dependent variable (audit delay) which can be explained by variability of independent variable (public account firm, complexity of company operations, and total assets) 31 % while the rest equal to 69 % is explained by other independent variables.